2014
DOI: 10.1007/s00403-014-1525-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of FCER1A genetic polymorphisms with risk for chronic spontaneous urticaria and efficacy of nonsedating H1-antihistamines in Chinese patients

Abstract: Antihistamines are the first-line treatment for chronic urticaria (CU). However, some CU patients are relatively refractory to antihistamines. The mechanism underlying the interindividual variation is still unknown. The α-chain of the high-affinity IgE receptor is crucial to the IgE-mediated allergic response. The present study is to investigate whether FCER1A polymorphisms are associated with the risk of CSU, and to determine whether these polymorphisms influence the therapeutic efficacy of nonsedating H1-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Additionally, our previous studies have determined the genetic polymorphisms that are associated with the risks of CSU susceptibility. For instance, FCER1A rs2298805G, ORAI1 rs3741596A and rs12313209T increased the risks to CSU susceptibility . CRP acted as an acute phase protein in inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, our previous studies have determined the genetic polymorphisms that are associated with the risks of CSU susceptibility. For instance, FCER1A rs2298805G, ORAI1 rs3741596A and rs12313209T increased the risks to CSU susceptibility . CRP acted as an acute phase protein in inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…All the patients were treated with non‐sedating H1 antihistamine monotherapy. The inclusion and exclusion criteria for enrolment were the same as in our previous studies . This study was approved by the Ethics Committee of Xiangya Hospital and was registered on the Chinese Clinical Trial Registry online (the registration number is ChiCTR‐OCH‐14004518).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional clinical associations for FCER1A SNPs are the putative association of the SNP rs2298804 with the risk of developing systemic lupus erythematosus in a study carried out in China (Yang et al, 2013 ), and the association of the SNP rs2298805 with the risk of developing chronic spontaneous urticaria in Chinese individuals (Guo et al, 2015 ). These SNPs are ethnic-specific as they have only been identified in Oriental individuals, but they do not occur in Caucasian individuals according to the 1000 genomes website.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely studied functional SNPs in ABCB1 gene is C3435T (rs1045642, ILe 1145ILe) in exon 26 [25], which also has a higher frequency in Chinese population than that in other ethnic groups including Caucasian and African populations [26][27][28]. Other research groups have reported of a correlation between genetic polymorphisms of allergic response proteins, such as IgE receptor (FCERIA) and component 5a receptor 1 (C5AR1), and the therapeutic efficacy or side effects of mizolastine in vivo [29][30][31]. But whether genetic variants of UGT1A1, CYP3A5 and ABCB1 are associated with pharmacokinetic interindividual variation of mizolastine and whether these variant genotypes influence the metabolic phenotypes of mizolastine is still unknown.…”
mentioning
confidence: 99%